Diet overlap among non‐native trout species and native cutthroat Trout (Oncorhynchus clarkii) in two U.S. ecoregions. Issue 6 (7th February 2021) - Minder, Mario; Arsenault, Emily R.; Erdenee, Bolortsetseg; Maasri, Alain; Pyron, Mark
Abstract: The invasion of freshwater ecosystems by non‐native species can constitute a significant threat to native species and ecosystem health. Non‐native trouts have long been stocked in areas where native trouts occur and have negatively impacted native trouts through predation, competition, and hybridization. This study encompassed two seasons of sampling efforts across two ecoregions of the western United States: The Great Basin in summer 2016 and the Yellowstone River Basin in summer 2017. We found significant dietary overlaps among native and non‐native trouts within the Great Basin and Yellowstone River Basin ecoregions. Three orders of invertebrates (Ephemeroptera, Trichoptera, and Diptera) composed the majority of stomach contents and were responsible for driving the observed patterns. Great Basin trout had higher body conditions (k), and non‐native Great Basin trout had higher gut fullness values than Yellowstone River Basin trout, indicating a possible limitation of food in the Yellowstone River Basin. Native fishes were the least abundant and had the lowest body condition in each ecoregion. These findings may indicate a negative impact on native trouts by non‐native trouts. We recommend additional monitoring of native and non‐native trout diets, regular invertebrate surveys to identify the availability of diet items, and reconsidering stocking efforts that can result in overlap of non‐native fishes with native cutthroat trout. Abstract : Non‐native trout in the western United States pose a significant threat to native trout species. We found significant dietary overlaps among native and non‐native trouts within the Great Basin and Yellowstone River Basin ecoregions. Selectivity analysis also suggested that native trout were more selective and may be adapting to non‐native trout pressure by selecting different diet items.